Antibodies binding the head domain of P2X4 inhibit channel function and reverse neuropathic pain. Issue 9 (September 2019) - Williams, Wendy A.; Linley, John E.; Jones, Clare A.; Shibata, Yoko; Snijder, Arjan; Button, James; Hatcher, Jon P.; Huang, Ling; Taddese, Bruck; Thornton, Peter; Schofield, Darren J.; Thom, George; et al.
Abstract : Abstract: P2X4 is a ligand-gated ion channel implicated in neuropathic pain. Drug discovery efforts targeting P2X4 have been unsuccessful largely because of the difficulty in engineering specificity and selectivity. Here, we describe for the first time the generation of a panel of diverse monoclonal antibodies (mAbs) to human and mouse P2X4, capable of both positive and negative modulation of channel function. The affinity-optimised anti-P2X4 mAb IgG#151-LO showed exquisite selectivity for human P2X4 and induced potent and complete block of P2X4 currents. Site-directed mutagenesis of P2X4 revealed the head domain as a key interaction site for inhibitory mAbs. Inhibition of spinal P2X4 either by intrathecal delivery of an anti-P2X4 mAb or by systemic delivery of an anti-P2X4 bispecific mAb with enhanced blood–spinal cord barrier permeability produced long-lasting (>7 days) analgesia in a mouse model of neuropathic pain. We therefore propose that inhibitory mAbs binding the head domain of P2X4 have therapeutic potential for the treatment of neuropathic pain. Abstract : Supplemental Digital Content is Available in the Text.Anti-P2X4 monoclonal antibodies binding the head domain of P2X4 potently and specifically inhibit channel function and reverse neuropathic pain by targeting spinal P2X4 in mice.